Investigation of the maximum dissolution rates and temperature dependence of a simulated UK nuclear waste glass in circum-neutral media at 40 and 90°C in a dynamic system. (July 2017) - Iwalewa, Tajudeen M.; Qu, Tingyu; Farnan, Ian
Abstract: This study investigates the influence of temperature on the dissolution of MW25, a non-radioactive simulant of UK Magnox glass. A single-pass flow-through (SPFT) system was used to measure the forward dissolution rate of MW25 at 40 and 90 °C and circum-neutral pH. The forward dissolution rate was found to be approximately one order of magnitude higher at 90 °C than at 40 °C. A similar release was observed for Si, Mg and Al at 40 °C and 90 °C, whereas the B, Cs, Na, Li and Mo showed an order of magnitude increase when the temperature was increased from 40 to 90 °C for low q/S values. The temperature dependence of the dissolution rates was determined using the Arrhenius rate law and the resultant activation energy (Ea ) shows that the dissolution process is a surface phenomenon. At 90 °C, the net effect of the processes governing MW25 dissolution led to preferential release of boron and alkali metals relative to the release of Si during the transient dissolution stage, accompanied by an increase in the concentration of silicic acid. This suggests that the solution activity of silicic acid at higher temperature has a weak influence on the release of the mobile elements. This study features a new method for estimating the surface area of reacted glass powder more accurately than the geometric surface area estimate, which is the preferred standard method among researchers. Highlights: The forward dissolution rates and temperature-dependence of MW25 was investigated at 40 and 90 °C. The forward rate was found to be approximately one order of magnitude higher at 90 °C than at 40 °C. The activation energy (Ea ) revealed that the dissolution process is surface control. The dependence of the dissolution rates on Si was found to be weak at 90 °C. This study presents a new method for estimating the surface area of reacted glass powder.